Spironolactone in Atrial Fibrillation With Preserved Cardiac Fraction: The IMPRESS‐AF Trial - Shantsila, Eduard (J Am Heart Assoc, 2020)
BACKGROUND: Patients with permanent atrial fibrillation have poor outcomes, exercise capacity, and quality of life even on optimal anticoagulation. Based on mechanistic and observational data, we tested whether the mineralocorticoid receptor antagonist spironolactone can improve exercise capacity, E/e' ratio, and quality of life in patients with permanent atrial fibrillation and preserved ejection fraction. METHODS AND RESULTS: The double‐masked, placebo‐controlled IMPRESS‐AF (Improved Exercise Tolerance in Heart Failure With Preserved Ejection Fraction by Spironolactone on Myocardial Fibrosis in Atrial Fibrillation) trial (NCT02673463) randomized 250 stable patients with permanent atrial fibrillation and preserved left ventricular ejection fraction to spironolactone 25 mg daily or placebo. Patients were followed for 2 years. The primary efficacy outcome was peak oxygen consumption on cardiopulmonary exercise testing at 2 years. Secondary end points included 6‐minute walk distance, E/e' ratio, quality of life, and hospital admissions. Spironolactone therapy did not improve peak oxygen consumption at 2 years (14.0 mL/min per kg [SD, 5.4]) compared with placebo (14.5 [5.1], adjusted treatment effect, −0.28; 95% CI, −1.27 to 0.71]; P=0.58). The findings were consistent across all sensitivity analyses. There were no differences in the 6‐minute walking distance (adjusted treatment effect, −8.47 m; −31.9 to 14.9; P=0.48), E/e’ ratio (adjusted treatment effect, −0.68; −1.52 to 0.17, P=0.12), or quality of life (P=0.74 for EuroQol‐5 Dimensions, 5‐level version quality of life questionnaire and P=0.84 for Minnesota Living with Heart Failure). At least 1 hospitalization occurred in 15% of patients in the spironolactone group and 23% in the placebo group (P=0.15). Estimated glomerular filtration rate was reduced by 6 mL/min in the spironolactone group with <1‐unit reduction in controls (P<0.001). Systolic blood pressure was reduced by 7.2 mm Hg (95% CI, 2.2–12.3) in the spironolactone group versus placebo (P=0.005). CONCLUSIONS: Spironolactone therapy does not improve exercise capacity, E/e' ratio, or quality of life in patients with chronic atrial fibrillation and preserved ejection fraction. REGISTRATION: UTL: https://www.clini​caltr​ial.gov; Unique identifier: NCT02673463. EudraCT number 2014‐003702‐33.